Information technology an introduction for today's digital world - Fox, Richard 1964- (CRC Press, 2013)
""Fox has delivered good, broad coverage of computer information technology suitable for use as a textbook for an introductory university course.""--Computing Reviews, July 2013 ""Deftly organized and presented, comprehensive, and extensive, and highly recommended for professional and academic library IT reference collections, Information Technology: An Introduction for Today's Digital World is ideal as an IT curriculum textbook.""--Midwest Book Review, April 2013